Application of care bundles in airway management for an elderly patient with severe pneumonia (集束化护理在1例高龄重症肺炎患者气道管理中的应用) - ZHANG Chunyan (张春艳); SHEN Juan (沈娟); ZHANG Ning (张宁); TANG Ling (唐玲); HUANG Po (黄坡); HAN Jianping (韩建萍); LI Ying (李影); YUE Yuzi (岳玉姿); REN Yaxing (任亚星); SUN Lei (孙磊) (中西医结合护理)
Severe pneumonia has a high incidence, fatality rate and poor prognosis in the elderly patients, which posing a great threat to the life safety of elderly patients. This article summarized the application experience of care bundles in an elderly patient with severe pneumonia. Through the development of clustered airway care measures, including effective sputum discharge, posture management, safe nasal feeding, oral care, and hand hygiene, in order to improve the patient’s prognosis. (重症肺炎在老年人中发病率、病死率高, 预后差, 对老年患者生命安全构成极大威胁。本文总结了集束化护理在1例高龄重症肺炎患者气道管理中的应用经验, 通过制定气道集束化护理措施, 包括有效排痰、体位管理、安全鼻饲、口腔护理、手卫生, 旨在改善患者预后。)